Characterisation of the native β-alanine pathway in Cupriavidus necator H16: an attractive route towards 3-hydroxypropionic acid production. - Orol Gómez, Diego (2020)
The sustainable production of chemicals and fuels through microbial fermentation will play a pivotal role in reducing our dependence on fossil resources as well as decreasing global emissions of greenhouse gases, and in particular CO2. A particularly promising strategy is to produce the requisite molecules using autotrophic microbial chassis that are capable of growing on CO2 as a sole carbon source. One such chassis is Cupriavidus necator H16, formerly Rastonia eutropha. It is a Gram-negative, non-pathogenic, asporogenous bacterium found in aerobic and anaerobic, non-halophilic environments. It is a facultative, chemolithoautotroph able to grow aerobically on CO2 and H2 as sole carbon and energy source, respectively. It can also grow heterotrophically on a variety of organic substrates.